Relationship factors influencing doctoral student retention and success: a study of faculty advisor and doctoral student perceptions - Fairbanks, Amanda Jo (Kansas State University, 2016)
Navigation and completion of a doctoral degree presents numerous challenges, including managing and understanding the faculty advisor/advisee relationship. Research shows faculty advisors are a critical aspect of the doctoral student experience; however faculty advisors and doctoral students do not always have the same perceptions of the advisor/advisee relationship. This study focused on measuring perceptions of faculty advisors and doctoral students in STEM and social science disciplines on various aspects of the advisor/advisee relationship. Likert-style survey items were used to measure perceptions of six constructs, advisor attributes and characteristics, roles and functions, relationship behaviors, and the faculty advisor role in student academic success, professional socialization, and engagement. Surveys were completed by 137 faculty advisors and 131 doctoral students. Analysis of data was conducted using various methods, including comparison of descriptive statistics, independent samples t-tests, and a factorial analysis of variance. Results of the data analysis revealed some significant differences between the perceptions of faculty advisors and doctoral students on several constructs. The discussion of results focuses on connections to current literature, as well as implications for future research and practice.
Keywords: Advisor/advisee relationship; Doctoral Retention; Graduate education; Faculty and student perceptions of advising; Advisor rolesDoctoral advising